2008
DOI: 10.1088/0953-8984/20/11/114121
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of Al–Mn, Al–Cu, and Al–Fe–Cu melts and their relations to liquid and quasicrystal structure

Abstract: Thermodynamic properties of molten Al-Mn, Al-Cu and Al-Fe-Cu alloys in a wide temperature range of 1123-1878 K and the whole range of concentrations have been studied using the integral effusion method and Knudsen mass spectrometry. Thermodynamic functions of melts were described by the associated solution model. The possibility of icosahedral quasicrystal (i-QC) precipitation from liquid Al-Mn and Al-Cu-Fe alloys was found to be a consequence of the existence in liquid associates (clusters). A geometric model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…1) For these reasons, the reaction abilities of elements, especially activity coefficient γAl of Al and γFe of Fe in Fe-Al binary melts have attracted tremendous attention in the past several decades. [2][3][4][5][6][7][8][9][10] Chipman and Floridis 2) measured the distribution of aluminum between liquid iron and silver, and combined these data to extrapolate activate coefficient γAl of . Using Knudsen cell-mass spectrometry, Belton and Fruhan 6) directly measured the activity of aluminum in liquid Fe-Al alloys up to 20.29 mass% Al at 1 873 K. Ichise et al 7) also used the same experimental technique to determine the activity of aluminum in liquid Fe-Al alloys up to 8.21 mass% Al in the temperature range from 1 673 K to 1 873 K. They reported the values of , , and in liquid iron as 0.049, 6.4, 0.017 and 8.2 at 1 873 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) For these reasons, the reaction abilities of elements, especially activity coefficient γAl of Al and γFe of Fe in Fe-Al binary melts have attracted tremendous attention in the past several decades. [2][3][4][5][6][7][8][9][10] Chipman and Floridis 2) measured the distribution of aluminum between liquid iron and silver, and combined these data to extrapolate activate coefficient γAl of . Using Knudsen cell-mass spectrometry, Belton and Fruhan 6) directly measured the activity of aluminum in liquid Fe-Al alloys up to 20.29 mass% Al at 1 873 K. Ichise et al 7) also used the same experimental technique to determine the activity of aluminum in liquid Fe-Al alloys up to 8.21 mass% Al in the temperature range from 1 673 K to 1 873 K. They reported the values of , , and in liquid iron as 0.049, 6.4, 0.017 and 8.2 at 1 873 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobson and Mehrotra 8) determined the activities of Fe and Al in Fe-Al alloys at 1 573 K using the ion-currentratio technique in a high-temperature Knudsen cell-mass spectrometry, and reported the values of and at 1 573 K as 0.016 and 0.019. In 2007, Kim et al 9) investigated the thermodynamics of aluminum in liquid iron in the temperature range of 1 873 K-1 973 K and reported the values of as 0.066, 0.069 and 0.071 at 1 873 K, 1 923 K and 1 973 K. Recently, Zaitsev et al 10) reported that three associative molecules as FeAl, FeAl2, and Fe2Al5 could exist in Fe-Al binary melts based on the experimental results using Knudsen cell-mass spectrometer and an integral variant of the effusion method under the condition of super high oil-free vacuum. But after checking previous literatures and phase diagram of Fe-Al binary system, Zhang 11) proposed that five molecules as Fe3Al, FeAl, FeAl2, Fe2Al5 and FeAl6 could exist in FeAl binary melts.…”
Section: Introductionmentioning
confidence: 99%
“…From thermodynamic point of view, binary systems Cu-Al, Cu-Mn and Al-Mn are well known, but ternary Cu-Al-Mn system is still the object of intensive investigations [13][14][15][16][17]. Cu-Al system was studied extensively by Murray and Liu [14,18,19].…”
Section: Introductionmentioning
confidence: 99%